Literasi Investasi Untuk Generasi Millenial Di Gresik - Handayani, Anita (JURNAL PENGABDIAN MANAJEMEN, 2023)
The purpose of the community service activities that have been carried out is related to literacy and investment. The investment literacy intended in this community service is investment literacy in the stock investment. This stock investment was introduced to the millennial generation to provide an overview regarding the importance of investing for young peopleand then the implementation of this stock investment for them. This investment literacy is carried out by the millennial generation in Gresik City. This community service activity is carried out in two stages, First, literacy stage by providing literacy to the importance of investing in the millennial generation. second, the implementation stage by investing through a securities company to be able to invest in stocks, because to be able to invest in shares a minimum of one hundred thousand rupiah.